Biotechnology Entrepreneurship Graduate Education Based in a Biology Department - Case Western Reserve University - Cullis, Christopher (Technology Transfer and Entrepreneurship (Discontinued), 2017)
Developing a Masters in Biotechnology entrepreneurship degree program based in a biology department provided some complex challenges. These challenges include convincing the faculty that the level of scientific competence of the graduating students is appropriate for a Masters' degree in that discipline. Since these degrees also feature biotechnology entrepreneurship, the business and entrepreneurship related expertise also needs to be addressed. The experience at Case Western Reserve University is a case study in how these challenges can be addressed so that the department granting the degree is comfortable with both the quality and outcome for the students. The program and the outcomes for the students and the department are described.
Keywords: Biotechnology